Brain-Based Learning and Multiple Intelligences as Related to Creative Dance Activities - Marcia Llyod, Lauralee Zimmerlee and Nicole Dean (Wacana Seni Journal of Arts Discourse, 2004)
The purpose of this article is to present connccticlns between Howard Gardner's (1983) Multiple Intelligences (MI) theory, brain-based research, and how one can apply this inforrnation in teaching and learning creative dance. While dance is the art form focused on by this article, many of the components discussed can be applied to drama, music, visual arts, other art forms, and physical education.